Augmented Reality Arabic Application For Preschool - Ainin Sofiya, Adnan (2023)
AR is a technology that places a computer-generated image on a user's perspective of the actual world, creating a composite image. Currently, a significant number of parents using this application for their children. Augmented Reality makes a difference in schooling. This application enables students to easily acquire, manage, and remember information, and it may also make studying more engaging. The name of this application is AR Arabic Application for Preschool. This application can assist parents in teaching their children the letters and numbers. This application has fulfilled the user requirement. Using AR education, kids may be more interested in this 3D model. The application is designed with Unity and the EasyAR package. This project's application development process is based on the RAD development model.